Socialization of The use of E-Commerce to Increase Student Income in Indonesia: Penelitian - Joice Soraya; Andy Mochamad Ramdan; Akbar Tanjung; Aswin Akbar; Nazmah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The author conducted this outreach program at several high schools with the most potential and quickest grasp of using e-commerce to increase revenue. These schools include MAN 2 Malang, SMAN 1 Pasundan, SMKN 1 Banten, and SMAN 2 Medan. The author believes that these seven materials are crucial for the participants of this outreach program. He hopes that this material will be utilized effectively and will foster a more creative and independent younger generation. Furthermore, he hopes this outreach program will spark the creation of young entrepreneurs in this country and address the current unemployment problem.